2008
DOI: 10.1111/j.1755-148x.2008.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

PPAR γ regulates MITF and β‐catenin expression and promotes a differentiated phenotype in mouse melanoma S91

Abstract: Melanoma represents one of the most rapidly metastasizing, hence deadly tumors due to its high proliferation rate and invasiveness, characteristics of undifferentiated embryonic tissues. Given the absence of effective therapy for metastatic melanoma, understanding more fully the molecular mechanisms underlying melanocyte differentiation may provide opportunities for novel therapeutic intervention. Here we show that in mouse melanoma S91 cells activation of the peroxisome proliferator activated receptor (PPAR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 63 publications
(71 reference statements)
3
33
0
Order By: Relevance
“…One possible mechanism might involve downregulation of the Wnt/b-catenin pathway because this pathway is inhibited by some PPARg agonists and might mediate the inhibition of MITF expression. 17,18 Thus, considering all our results we show for the first time that the control of MITF expression by ciglitazone is involved in the inhibition of CXCL1 expression and secretion. This new signaling pathway involves MITF in the regulation of CXCL1 and strengthens the importance of this transcription factor in melanoma tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible mechanism might involve downregulation of the Wnt/b-catenin pathway because this pathway is inhibited by some PPARg agonists and might mediate the inhibition of MITF expression. 17,18 Thus, considering all our results we show for the first time that the control of MITF expression by ciglitazone is involved in the inhibition of CXCL1 expression and secretion. This new signaling pathway involves MITF in the regulation of CXCL1 and strengthens the importance of this transcription factor in melanoma tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the mechanism responsible for ciglitazone-induced CXCL1 downregulation, we focused our attention on MITF that was recently reported to be regulated by some PPARg agonists. 17,18 Ciglitazone induced a dose-dependent reduction of MITF expression in both A375 and SK-Mel-28 melanoma cells (Figure 7a). We demonstrated that MITF inhibition by ciglitazone was not due to its cleavage during Cytokines Chemokine (C-X-C motif) ligand 1 (melanoma growth-stimulating activity, a) Negative regulation of MITF/CXCL1 axis by TZD T Botton et al apoptosis because the MITF decrease was observed earlier than PARP cleavage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that fenofibrate plays important role in anticancer properties via diverse mechanisms in recent years (Balfour et al, 1990;Pawlik et al, 2004;Saidi et al, 2006;Grabacka et al, 2006;Urbanska et al, 2008;Zak et al, 2010;Wilk et al, 2012;Cho et al, 2013;Zhao et al, 2013;Liang et al, 2013;Watanabe et al, 2013;Li et al, 2014). But the exact relationship between fenofibrate and irradiation has not explored.…”
Section: Jia Liu Et Almentioning
confidence: 99%
“…Interestingly, more recent studies suggest that fenofibrate may have an important role as antitumor agents in various cancers such as glioblastoma (Wilk et al, 2012), prostate cancer (Zhao et al, 2013), lung cancer (Liang et al, 2013), breast cancer (Li et al, 2014), endometrial cancer (Saidi et al, 2006), colon cancer (Watanabe et al, 2013), melanoma (Grabacka Jia Liu et al et al, 2006), medulloblastoma (Urbanska et al, 2008) and leukemia (Zak et al, 2010). Fenofibrate decreases metastatic potential of melanoma cells in vitro via downregulation of Akt (Grabacka et al, 2006). Fenofibrate induced apoptosis and decreased proliferation rate in endometrial cancer cells (Saidi et al, 2006), in human and mouse medulloblastoma cell lines (Urbanska et al, 2008), in mantle cell lymphoma (Zak et al, 2010), and in triple-negative breast cancer cells (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%